Strategia kontroli kosztów w niemieckim banku spółdzielczym - Ostojski, Wojciech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main purpose of a paper is to present the strategy of cost control. The article shows the characteristic and the strategy of German cooperative bank. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 310-317